Best Answer

3ab + 3ac + 2b2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)

Q: Factor 3ab plus 3ac plus 2b squared plus 2bc?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

Related questions

(3a - 2c)(b - d)

3a(b+c)+2b(b+c)

(a+b)(3b+1)

6

(3b - 1)(a - b)

12ab+3ab=15ab

(3b - 1)(a - b)

Factorizing 3ab + 3ac gives 3a (b + c).Factorizing is to express a number or expression as a product of factors.When factorizing always look for common factors. To factorize (3ab + 3ac) look for the highest factor between the two terms (3a). 3ab + 3ac = 3a (b + c)

3ab - a - 3b2 + b = -3b2 + 3ab + b - a = -3b(b - a) + 1(b - a) = (1 - 3b)(b - a)

It is: 3ab

3ab[35 - 4]

-2ab